Public Speaking serta Teknik Ice Breaking dan MC Sebagai Upaya Pengajaran yang Menarik - Rudi Kristanto; Sudarwanto Sudarwanto; Wahyuni Kurniawati (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
Methods of public speaking and ice breaking, master of ceremonies (MC), or "master of ceremonies" are very important to support activities that are often carried out in an institution or institutions, both governmental and non-governmental organizations in activity both formal or activity on formal at every activity event. Students often feel less touched by the teaching methods presented so there is a need for creativity in communication that has an impact on the effectiveness and is interesting in the teaching and learning process.        Public speaking, can improve expertise in academics and careers, improve communication skills in general. Public Speaking will develop and improve communication skills, improve speaking skills in front of an audience. The speaker is not born but is created. Ice-breaking can create conditions that are equal or equal to fellow trainees, eliminating gaps or boundaries between participants, so there are no differences so that similarities and opportunities for progress arise. The Master of Ceremonies MC was introduced by the SAPA method (Greetings and Greetings, Appreciation, Introductions, Attention and Event Description). This method is easy to remember and easy to memorize.         All the participants felt the benefits and said that the event was lacking in time. So it was felt that it was necessary to make similar activities aimed at providing soft skills to all audiences